The Effect of Liquidity, Leverage, Cash Flow, Earning Growth, Firm Size, and Risk on Financial Health - Ike Prety Shinta; Triyono (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
A company's financial health is vital for sustaining its operations, especially in the face of economic uncertainty and sector-specific challenges. This study seeks to address a critical research gap by examining the determinants of financial health specifically in manufacturing companies within the basic and industrial sectors listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period a time marked by post-pandemic recovery and disruptions in global supply chains. The study employs the Altman Z-score model, traditionally used for bankruptcy prediction, as a comprehensive indicator of financial health due to its ability to synthesize multiple financial dimensions. To investigate the influence of liquidity, leverage, cash flow, earning growth, firm size, and financial risk on financial health, multiple linear regression analysis is conducted. These independent variables are operationalized as follows: liquidity is measured by the current ratio, leverage by the debt-to-equity ratio, cash flow by net operating cash flow, earning growth by year-over-year changes in net income, firm size by the natural logarithm of total assets, and financial risk by the variability of earnings. Data were obtained through purposive sampling based on the availability of complete financial reports during the observation period, resulting in a sample of manufacturing firms that met the inclusion criteria. The results indicate that liquidity, cash flow, and financial risk significantly affect financial health, whereas leverage, earnings growth, and firm size do not demonstrate a meaningful impact.